O Kaus de Jorge Mautner: escrita e temporalidade (1950-1960) - Chaves, Reginaldo Sousa (2019)
In the present work we establish the historical reading of Jorge Mautner’s literature and of what he calls Kaos. In view of this, we seek to problematize the archiving of his life and work in the condition of "proto-tropicalists", from 1970. Thus, we discuss how Tropicalism went from allegorical explosion to institutionalized cultural monument and in what way the Mautnerian trajectory was saturated to this "movement". For this, we seek to release other interpretative possibilities of his scriptural production that are beyond the classification as "precursor" of Tropicália. Next, we establish a distinctive series in which Mautner's production resonates with others that belong to the modern Brazilian artistic culture of the fifties and sixties. In this way, we are talking about the construction of a historical-cultural atlas based on the discussion of concretist, surrealist, beat-surrealist and cepecist works and artists responsible for contributing to the configuration of conflicting polarities that formed a dialectical field: revolution and rebellion, militancy and alienation, archaic and modern. Given that at the center of these contradictions are the varied scriptural practices with their organization forms of the relations between past, present and future, which are confronted with the teleologies of their time. With this, it is from this historical collection that we show how Mautner proposes his novels as literary montages of diverse political mythologies and temporalities. Thus, the Kaos shows itself as a discussion of romanticism, body, sexuality, youthful rebellion, revolution, and insurgent people. Therefore, through a network reading, we confront the time constellation of other intellectuals such as Mário Schenberg, Vicente Ferreira da Silva and Oswald de Andrade, who imagined a world in which mythical leisure (past) and technical world (future) would combine with temporal policies that were in close connection with the ideals of Kaos.